PROCESS WAREHOUSE BASED RESOURCE EVALUATION APPROACH FOR BUSINESS PROCESS ANALYSIS - SOHAIL, ABID (2015)
Business process improvement is a systematic approach used by enterprises to achieve a competitive edge. A key aspect of improving the executed performance of a process is to assign the most appropriate resources to each process task. During process execution, process traces are generated which are widely acknowledged as important sources for posterior analysis. One type of posterior analysis is 'process mining', another is 'process warehouse'. However, information provided by process mining does not yield either tempting or attractive analytical relativism compared to process warehouse because process mining inevitably provides similar solutions due to the limitations of data availability and to unstructured data organization.